PENERAPAN KESELAMATAN KERJA RADIASI PADA SISTEM PELAYANAN FLUOROSKOPI BAGASI DI BANDARA INTERNASIONAL AHMAD YANI SEMARANG - Sri Mulyati; M. Irwan Katili; Yeti Kartikasari (Jurnal LINK, 2016)
Application of used of X-ray fluoroscopy baggage aims to detect passenger baggage before going to the airport. However, the use of fluoroscopy baggage needs special attention because it involves the use of electromagnetic radiation energy is quite high (140-180 kV) that can cause biological effects against those X-ray worker or general public. Therefore, community service is intended to disseminate research results through lectures, discussions and demonstrations about radiation safety efforts on Fluoroscopy Baggage. Welcoming ceremony and the enthusiasm of the participants comprising of components airport management, security (AVSEC) and some of the workers who were around the fluoroscopy baggage, understanding of the performance of radiation used tools, understand the biological effects of radiation, and understand the importance of radiation safety in the use of fluoroscopy baggage. In addition to the demonstration session participants introduced some radiation monitoring devices (TLD Badge, Film Badge, Pen Dosimeter) and a radiation measuring instrument (Ram Ion Surveymeter).